Analysis And Prevention of Pb Metal Content Suspended In Belawan Waters - Mardame Pangihutan Sinaga; Ady Frenly Simanullang (Politeknik Negeri Batam, 2021)
The study of Pb in suspended solid and dissolved in the Belawan Port Waters was conducted on June until November 2021. Analysis of Pb content in suspended solid was mesured at Laboratory of Environmental Health and Disease Control Engineering Center (BTKLPP) in North Sumatra Province. Pb content in suspended solid at high tide ranged from <0,02-0,06 mg/l and at low tide ranged from 0,02-0,065 mg/l. The content of dissolved Pb at high tide ranged from 0,210-0,651 mg/l and at low tide ranged from 0,288-0,750 mg/l. Content of Pb in the waters of Belawan Port has passed quality standard of the Minister of Environment of Republic Indonesia that means the Harbour area is polluted and improper for drinking water as well as for fish cultivation.